The Relationship of Craniofacial Structure Changes in Mouth Breathing Patients to Pharyngeal Airway Dimensions: A Lateral Cephalometric Study - Lubis, Mimi Marina; Bahirrah, Siti; Lubis, Hilda Fitria; Rumaisha, Khalila (Journal of Syiah Kuala Dentistry Society, 2025)
Background: Prolonged airway obstruction during facial growth can influence the development of craniofacial structures. Conversely, craniofacial deformities may contribute to reduced airway dimensions. Understanding the relationship between craniofacial morphology and pharyngeal airway space is essential, particularly in individuals with altered breathing patterns such as mouth breathing. Objective: This study aimed to determine the differences and relationships between craniofacial structures and pharyngeal airway dimensions in patients with mouth breathing compared to those with normal nasal breathing. Methods: This study employed a descriptive-analytic research design. A total of 20 lateral cephalograms were analyzed10 from patients with normal breathing and 10 from mouth-breathing patients, all presenting with skeletal class II malocclusion. Landmarks were identified manually, and measurements were carried out using the CorelDRAW application. The Unpaired T-test was used to assess differences between groups. The Pearson correlation test was used to examine the relationship between craniofacial structures and airway dimensions in the mouth-breathing group. Results: Significant differences were found in mandibular structure and the oropharyngeal U-MPW plane angle (p 0.05) between mouth breathers and nasal breathers. However, no statistically significant correlation was observed between craniofacial measurements and pharyngeal airway dimensions within the mouth-breathing group. Conclusion: This study concludes that increased anteroposterior skeletal measurements and vertical facial height are not significantly associated with narrowing of pharyngeal airway dimensions in mouth-breathing patients. Further studies with larger sample sizes are recommended to explore this relationship more comprehensively.